Peanut meal and crude glycerin in lamb diets: Meat quality and fatty acid profile - Valença, Roberta de Lima [UNESP] (2020)
This study aimed to evaluate the effects on lamb meat quality of replacing the soybean meal and corn diet with peanut meal and crude glycerin. A total of 40 lambs, with an initial body weight of 17.15 ± 1.56 kg, were divided into four biodiesel by-product treatment groups: a no-treatment control, peanut meal, crude glycerin, and peanut meal + crude glycerin. The roughage-to-concentrate ratio was 40:60 in all diets. Peanut meal, crude glycerin, and their combination had no effect on the physicochemical characteristics of the meat, except the fatty acid profile. The meat from animals fed the diets with crude glycerin and peanut meal + crude glycerin had higher proportions of oleic, pentadecanoic, heptadecanoic, and eicosapentaenoic fatty acids, lower proportions of palmitic acid, a lower atherogenicity index, a lower sum of hypercholesterolemic fatty acids, and stronger hypocholesterolemic:hypercholesterolemic relationships. When used as alternative sources of protein and energy in the diet of feedlot lambs, peanut meal and crude glycerin improve the lipid profile of the meat.